2008
DOI: 10.1093/qjmed/hcn078
|View full text |Cite
|
Sign up to set email alerts
|

Factors that affect longevity of intravenous cannulas: a prospective study

Abstract: IC gauge and site of placement are important factors in determining IC longevity. 18 g ICs placed in the forearm/wrist can considerably increase the longevity of ICs and should be attempted in patients who require sustained cannulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 13 publications
4
34
0
6
Order By: Relevance
“…In numerous studies, the prolonged cannula dwell time in situ significantly increased the development of phlebitis on observed PVCs (Abbas, de Vries, Shaw, & Abbas, ; Cicolini et al, ; Dillon et al, ; Do Rego Furtado, ; Maki & Ringer, ; Malach et al, ). Several previous studies and our study have found that the probability of developing phlebitis is about twice greater if the cannula dwell time is longer than 72 hr compared to PVC up to 24 hr in situ (Abbas et al, ; Do Rego Furtado, ).…”
Section: Discussionmentioning
confidence: 99%
“…In numerous studies, the prolonged cannula dwell time in situ significantly increased the development of phlebitis on observed PVCs (Abbas, de Vries, Shaw, & Abbas, ; Cicolini et al, ; Dillon et al, ; Do Rego Furtado, ; Maki & Ringer, ; Malach et al, ). Several previous studies and our study have found that the probability of developing phlebitis is about twice greater if the cannula dwell time is longer than 72 hr compared to PVC up to 24 hr in situ (Abbas et al, ; Do Rego Furtado, ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the site chosen to insert the device, the forearm (36.7%) was the preference of the nursing team due to the presence of long and large veins that enable the insertion of catheters with higher calibres (7,18) . A study shows that there is no indication of the ideal anatomic region to reduce the risk of phlebitis.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,7,13 Pesquisas mostraram que a taxa dessa complicação local não aumenta com o tempo de permanência do CIP. [23][24][25] Quanto à região anatômica e a ocorrência de flebite, não se observou associação significativa (p=0,059). O antebraço foi o local de punção mais utilizado pela equipe de enfermagem.…”
Section: Discussionunclassified
“…A preferência por essa região, também evidenciada em outras investigações, encontra-se relacionada à presença de veias calibrosas e longas, como cefálica e basílica, que possibilitam a inserção de CIP mais calibrosos. 4,12,24 O fato de esses acessos terem sido puncionados principalmente com CIP de 18G e 20G, pode ter, de certo modo, evitado a flebite. Atualmente não existe consenso acerca da região anatômica ideal ou de menor risco de flebite.…”
Section: Discussionunclassified